The tools for successful online teaching - Dawley, Lisa, 1960- (Hershey : Information Science Pub., 2007)
'This book is a guide for those desiring more in-depth study of how to integrate a variety of internet technology tools for successful online learning. This is an excellent resource for all online teach ers, and those who design curricula for online environments'--Provided by publisher
Includes bibliographical references and index
Keywords: Computer-assisted instruction; Internet in education; Education -- Computer network resources